2012
DOI: 10.1097/rlu.0b013e3182443110
|View full text |Cite
|
Sign up to set email alerts
|

Early Dynamic PET/CT and 18F-FDG Blood Flow Imaging in Bladder Cancer Detection

Abstract: Early dynamic FDG PET images can demonstrate bladder lesions that are obscured by urine activity on routine images at 1 hour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…In an effort to improve tumor conspicuity through an increase of tumor-to-urine SUVmax ratio, few authors have investigated the utility of early dynamic acquisitions, before radioactive urine has had a chance to fill the bladder (13,67,68). In these proof-of-concept studies, the authors suggested that such dynamic acquisitions might improve tumor detection and staging; however, the impact on LN staging was not evaluated.…”
Section: Early Dynamic Acquisitionsmentioning
confidence: 99%
“…In an effort to improve tumor conspicuity through an increase of tumor-to-urine SUVmax ratio, few authors have investigated the utility of early dynamic acquisitions, before radioactive urine has had a chance to fill the bladder (13,67,68). In these proof-of-concept studies, the authors suggested that such dynamic acquisitions might improve tumor detection and staging; however, the impact on LN staging was not evaluated.…”
Section: Early Dynamic Acquisitionsmentioning
confidence: 99%
“…However, this protocol intrinsically contains a masking effect of the tracer in the urine and renal parenchyma. Technical developments in FDG-PET/ CT with early dynamic (ED) scans have enabled the estimation of tumour blood flow in hepatocellular carcinoma [10,11], pancreatic cancer [12] and bladder cancer [13]. The ability to estimate tumour blood flow and metabolic activity from a single FDG-PET/CT study may enhance the ability to detect and characterize RCC tumours.…”
Section: Introductionmentioning
confidence: 99%
“…This technique was noninvasive and could improve the detection of locally recurrent or residual bladder tumors; however, furosemide must be injected at least 2 hours after radiotracer injection, and many delayed images must be taken (6). In addition, early dynamic FDG PET images can demonstrate the presence of bladder lesions that are obscured by urine activity on routine images taken 1 hour after a radiotracer is injected (13).…”
Section: Discussionmentioning
confidence: 99%